THE ROLE AND IMPORTANCE OF FOLK MEDICINE IN THE FERGANA VALLEY AT THE END OF THE 19TH AND THE BEGINNING OF THE 20TH CENTURY (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article examines the role and significance of folk medicine in the lives of the local population of the Fergana Valley at the turn of the 19th and 20th centuries. It analyzes the main forms and methods of traditional healing, the functions of tabibs (folk healers), and the medicines they employed. Particular attention is given to the colonial policies of the Russian Empire, which did not directly restrict traditional medicine but promoted Western medical institutions in the region. Drawing on archival materials, periodicals, and scholarly works, the study argues that folk medicine continued to play a crucial role in the daily lives of the rural population despite the gradual introduction of Russian medical practices.